Tokyo shitamachi: Tatekawa - Dantas, Paulo (2025)
A simple composition using underwater stereo recordings from the Tatekawa, a river flowing into Tokyo’s Sumida River. Originally created for Mieko Matsumoto’s video in the Breathing Particles exhibition at TOKAS Hongo Gallery, Tokyo (July–August 2024). Above the river lies the Shuto Expressway, an elevated highway built for “practicality,” accelerating the river’s original transportation functions. From within the Tatekawa, the expressway’s intense activity and maintenance work are audible. On quieter days, with the use of filters, some species adapting to these changes can still be heard. These recordings layer different times and speeds in the urban “now”: the natural rivers, now channeled, and their modern counterparts—the expressways immortalized by Tarkovsky and Oshii. Distant sine wave allusions to Hana, a Western-style song by Rentaro Taki, emerge, as if engulfing the Tatekawa’s sounds.
FRIS
1
Keywords: Music, Thought and Technology